Effect of coumarin on carrion decomposition and its secondary bioaccumulation in Chrysomya rufifacies larvae - M, Othman; Nor Aliza, Abdul Rahim; Zainab, Ngaini (Malaysian Society of Parasitology and Tropical Medicine (MSPTM), 2025)
The presence of chemical substances can interfere with the insect activities, affecting the decomposition duration of carrion, thus under-estimating the minimum post-mortem interval. This study investigates the effects of coumarin an active ingredient in anti-coagulant rodenticide, on carrion decomposition and secondary bioaccumulation in fly larvae tissue. Twenty-four rat carcasses were divided into control (CR) and coumarin-treated (TR) groups, and their decomposition stages were observed under identical environmental conditions. Results indicate that coumarin delayed the decomposition by approximately four days, primarily due to its impact on insect arrival and larval activity. Chrysomya rufifacies (Macquart, 1843) (Diptera: Calliphoridae) was the predominant species in both groups, with slower larval feeding on TR carcasses prolonging the transition from active to advanced decay. Secondary bioaccumulation of coumarin in third-instar larvae was detected using Gas Chromatography-Mass Spectrometry (GC-MS). These findings highlight coumarin’s potential to alter insect succession patterns and its implications for minimum post-mortem interval (minPMI) estimation in forensic investigations.